2016
DOI: 10.3389/fpsyg.2016.01760
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Deprivation Negatively Impacts Children’s Prosocial Behavior

Abstract: Children show stronger cooperative behavior in experimental settings as they get older, but little is known about how the environment of a child shapes this development. In adults, prosocial behavior toward strangers is markedly decreased in low socio-economic status (SES) neighborhoods, suggesting that environmental harshness has a negative impact on some prosocial behaviors. Similar results have been obtained with 9-year-olds recruited from low vs. high SES schools. In the current study, we investigate wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 40 publications
3
28
1
Order By: Relevance
“…They found that people living in lower SES neighborhoods were less generous in economic games, had lower social capital and showed more antisocial behavior. Safra et al (2016) replicated this finding in 6 to 7 year-old children living in neighborhoods differing on overall SES but not other characteristics. They found that children living in harsher environments behaved less prosocially towards strangers in the context of a dictator game adapted to children.…”
Section: Introductionsupporting
confidence: 54%
“…They found that people living in lower SES neighborhoods were less generous in economic games, had lower social capital and showed more antisocial behavior. Safra et al (2016) replicated this finding in 6 to 7 year-old children living in neighborhoods differing on overall SES but not other characteristics. They found that children living in harsher environments behaved less prosocially towards strangers in the context of a dictator game adapted to children.…”
Section: Introductionsupporting
confidence: 54%
“…However, the literature in this area is very recent. Other studies have found the inverse pattern of results (Benenson et al., ; Safra et al., ). The causes (and consequences) of socioeconomic differences in children's perceptions of exclusive relations between high‐ and low‐wealth groups are fruitful areas for future research.…”
Section: Discussionmentioning
confidence: 79%
“…Importantly, it is not yet known whether children from higher income backgrounds also hold these attitudes. Research on relations between family economic status and children's prosocial behavior, for example, has revealed both negative (Chen, Zhu, & Chen, ; Miller, Kahle, & Hastings, ) and positive (Benenson, Pascoe, & Radmore, ; Safra et al., ) relations. However, exposure to norms encouraging the promotion of one's own interests may make higher income children more likely to expect that groups (of any economic background) would try to gain access to opportunities when they have the chance.…”
Section: Children's Perceptions Of Economic Groupsmentioning
confidence: 99%
“…Importantly, life history theory predicts that cooperative behaviors should be part of a more general life history strategy. In line with this prediction, Petersen and Aarøe (2015) report an association between low birth weight, low self-control in childhood, and lower social trust in adulthood (on the early calibration of prosociality, see also Benenson et al 2007;Safra et al 2016). Similarly, lab studies show a correlation between high time discountingan indicator of a faster life strategyand low levels of cooperation in economic games (Curry et al 2008;Espín et al 2012;Harris & Madden 2002;Kocher et al 2013;Kortenkamp & Moore 2006).…”
Section: Trustmentioning
confidence: 85%